The obesity-linked human lncRNA AATBC stimulates mitochondrial function in adipocytes - Giroud Maude; Kotschi Stefan; Kwon Yun; Le Thuc Ophelia; Hoffmann Anne; Gil-Lozano Manuel; Karbiener Michael; Higareda-Almaraz Juan Carlos; Khani Sajjad; Tews Daniel; Fischer-Posovszky Pamela; Sun Wenfei; et al. (Embo Press, 2025)
Adipocytes are critical regulators of metabolism and energy balance. While white adipocyte dysfunction is a hallmark of obesity-associated disorders, thermogenic adipocytes are linked to cardiometabolic health. As adipocytes dynamically adapt to environmental cues by functionally switching between white and thermogenic phenotypes, a molecular understanding of this plasticity could help improving metabolism. Here, we show that the lncRNA Apoptosis associated transcript in bladder cancer (AATBC) is a human-specific regulator of adipocyte plasticity. Comparing transcriptional profiles of human adipose tissues and cultured adipocytes we discovered that AATBC was enriched in thermogenic conditions. Using primary and immortalized human adipocytes we found that AATBC enhanced the thermogenic phenotype, which was linked to increased respiration and a more fragmented mitochondrial network. Expression of AATBC in adipose tissue of mice led to lower plasma leptin levels. Interestingly, this association was also present in human subjects, as AATBC in adipose tissue was inversely correlated with plasma leptin levels, BMI, and other measures of metabolic health. In conclusion, AATBC is a novel obesity-linked regulator of adipocyte plasticity and mitochondrial function in humans.